PARE0027 PATIENT PERSPECTIVE ON INTRA-ARTICULAR THERAPIES IN RMDS: RESULTS FROM A EUROPEAN SURVEY. (2nd June 2020) - Pitsillidou, I.; De la Torre-Aboki, J.; Uson Jaeger, J.; Naredo, E.; Terslev, L.; Boesen, M.; Pandit, H.; Möller, I.; D'agostino, M. A.; Kampen, W. U.; O'neill, T.; Doherty, M.; et al.
Abstract : Background: Intra-articular therapy (IAT) is routinely used in rheumatic and musculoskeletal diseases (RMDs). In order to improve the effectiveness and safety of IAT, it is essential to understand patients' perceptions and needs. Objectives: To assess the perspective of persons who have experienced IAT, including perceptions on benefits and safety. Methods: A steering committee (including a patient research partner) prepared a 44-item questionnaire based on the information needs of a Taskforce on IAT in adult patients with RMDs. The questionnaire was translated into 11 languages and disseminated via EULAR PARE associations and social media. Persons who had experienced at least two IAT procedures were eligible for the survey. Descriptive statistics were used to summarise results as well as inductive codification of open-ended questions. Results: The survey was answered by 200 individuals diagnosed with rheumatoid arthritis (66%), osteoarthritis (21%), spondyloarthritis (10%), psoriatic arthritis (9%), and others (16%). The mean number of IATs received was 7 (SD 8), mainly in the knee (66%), shoulder (42%), and wrist (28%), and primarily with corticosteroids (83%) or hyaluronic acid (16%). Twenty-seven percent had not been informed about benefits or potential complications of IAT, and 73% had not been asked whether they wanted local anaesthetic. Consent was deemed necessary by 82 (41%). Most (65%) had never received an ultrasound (US)-guided injection, and of those who had experienced blinded and guided injections, 42 (63%) preferred US-guided because of increased perceived accuracy and confidence in the procedure. Only 50% reported a clear benefit of IAT, mainly in terms of reduced pain and increased joint mobility, but also perceived reduced inflammation, with effect from immediate to 36 hours or even 3 weeks post-injection, and that lasted from as little as less than one week to years. Regarding safety, 40 (20%) had experienced some complications from IAT, including but not limited to increased pain, impaired mobility, rashes, or swelling. Finally, the respondents suggested improvements in the procedure, including: (1) wider availability; (2) less painful procedures; (3) greater efficacy, faster and longer-lasting; (4) fewer side effects; (5) a clear diagnosis beforehand; (6) better shared decision-making, including better information; (7) follow-up, (8) better accuracy; and (9) more expertise. Conclusion: The survey has identified gaps in the IAT procedures, such as a need for clearer information. Patients perceive IAT as relatively safe, though painful, and with varying effect. Suggestions for improving the procedure, including more expertise, should be relayed to professionals and relevant organisations. Acknowledgments: Eular Taskforce grant CL109 Disclosure of Interests: IRENE Pitsillidou: None declared, Jenny de la Torre-Aboki: None declared, Jacqueline Uson Jaeger: None declared, Esperanza Naredo: None declared, Lene Terslev: None declared, Mikael Boesen Consultant of: AbbVie, AstraZeneca, Eli Lilly, Esaote, Glenmark, Novartis, Pfizer, UCB, Paid instructor for: IAG, Image Analysis Group, AbbVie, Eli Lilly, AstraZeneca, esaote, Glenmark, Novartis, Pfizer, UCB (scientific advisor)., Speakers bureau: Eli Lilly, Esaote, Novartis, Pfizer, UCB, Hemant Pandit Grant/research support from: Glaxo Smith Kline (GSK) for work on Diclofenac Gel, Speakers bureau: Bristol Myers Squibb for teaching their employees about hip and knee replacement, Ingrid Möller: None declared, Maria Antonietta D'Agostino Consultant of: AbbVie, BMS, Novartis, and Roche, Speakers bureau: AbbVie, BMS, Novartis, and Roche, Willm Uwe Kampen: None declared, Terence O'Neill: None declared, Michael Doherty Grant/research support from: AstraZeneca funded the Nottingham Sons of Gout study, Consultant of: Advisory borads on gout for Grunenthal and Mallinckrodt, Francis Berenbaum Grant/research support from: TRB Chemedica (through institution), MSD (through institution), Pfizer (through institution), Consultant of: Novartis, MSD, Pfizer, Lilly, UCB, Abbvie, Roche, Servier, Sanofi-Aventis, Flexion Therapeutics, Expanscience, GSK, Biogen, Nordic, Sandoz, Regeneron, Gilead, Bone Therapeutics, Regulaxis, Peptinov, 4P Pharma, Paid instructor for: Sandoz, Speakers bureau: Novartis, MSD, Pfizer, Lilly, UCB, Abbvie, Roche, Servier, Sanofi-Aventis, Flexion Therapeutics, Expanscience, GSK, Biogen, Nordic, Sandoz, Regeneron, Gilead, Sandoz, Valentina Vardanyan: None declared, Elena Nikiphorou: None declared, Sebastian C Rodriguez-García Speakers bureau: Novartis Farmaceutica, S.A., Merck Sharp & Dohme España, S.A., Sanofi Aventis, UCB Pharma, Raul Castellanos-Moreira: None declared, Loreto Carmona Grant/research support from: Novartis Farmaceutica, SA, Pfizer, S.L.U., Merck Sharp & Dohme España, S.A., Roche Farma, S.A, Sanofi Aventis, AbbVie Spain, S.L.U., and Laboratorios Gebro Pharma, SA (All trhough institution)